Microbiota, chronic inflammation, and health: The promise of inflammatome and inflammatomics for precision medicine and health care - Zhang, Huan (Elsevier B.V., 2025)
The terms “inflammatome” (holistic inflammation networks) and “inflammatomics” (a novel omics field) were proposed to decode dysbiosis-driven chronic inflammation and its disease links. Inflammatomics explores microbiota–immune crosstalk, particularly innate immune interactions, revealing how dysregulated microbial communities trigger chronic inflammation underlying disorders like inflammatory bowel disease, metabolic diseases, and neurodegeneration. This discipline transcends traditional inflammation paradigms by dissecting molecular pathways connecting dysbiosis to systemic inflammation, enabling early detection and precision interventions. It integrates evolutionary perspectives on host–microbe interactions, emphasizing the human body as a stress-sensitive “organ”. Challenges include standardizing inflammatome profiling, translating findings into clinical tools, and advancing multiomics technologies. By bridging microbial ecology, immunology, and systems medicine, inflammatomics holds a transformative potential to shift health care from reactive treatment to proactive, personalized prevention, targeting disease origins shaped by chronic inflammatome dysregulation.